The effects of the EU Fit for 55 package on labour markets and the demand for skills - Borgonovi, Francesca (OECD Publishing, 2023)
This paper quantifies changes in employment and the demand for skills in the European Union following the implementation of Fit for 55 policies. Between 2019 and 2030, the economy is projected to grow by 1.3% in the Fit for 55 scenario (3% in a Baseline scenario without the Fit for 55 policies). Employment growth is projected to be lower in the Fit for 55 than the Baseline scenario. Employment in the Fit for 55 scenario is projected to decrease by 3% for blue collar and farm workers (2% in the Baseline) and increase by 4 5% for other occupations (5-6% in the Baseline). The most demanded skills following the implementation of Fit for 55 will be those related to inter personal communication and the use of digital technologies, whereas the demand for skills related to the use of traditional tools and technologies is projected to decline. Anticipating changes in employment and the demand for skills as well as the socio-demographic profile of those most affected can facilitate the design of upskilling and reskilling efforts and promote the reallocation of workers across sectors and occupations
Keywords: Employment; Environment; Social Issues/Migration/Health